Blended-Contextual Teaching and Learning: Bagaimana Efektivitasnya Terhadap Kemandirian Belajar dan Pemahaman Konsep Siswa pada Materi Ekosistem? - Ladisa Cikal Asa Bangsa; Ummi Nur Afinni Dwi Jayanti (BIOEDUSCIENCE, 2022)
Background: Blended-Contextual Teaching and Learning is a combination of contextual learning models with blended learning. The learning that is created is the concept of a contextual model where the teacher acts as a facilitator and moderator and does not tend to present something already finished to students. This analysis is aimed to determine the effectiveness of the Blended-Contextual Learning model on the freedom and understanding of the concepts of high school students in class X Ecosystem material.. Methods: In this research, the quantitative research method was used using experimental research and research design, namely Quasi-Experimental Design, using an assessment instrument that has been tested for validity. The research was conducted at Madrasah Aliyah with a sample of 48 students. Results: Blended-Contextual Learning effectively increases the independence and students' conceptual understanding ability treated with the Blended-Contextual Learning model. Conclusions: Blended-Contextual Teaching and Learning has a practical effect because it has a positive influence on stimulating an increase in student's conceptual understanding, as seen in the data analysis above, which shows an increase in conceptual understanding in the treated class.